(untitled) (Global Journal of Human-Social Science, 2023)
Illicit Financial Flows also knowns as Capital Flight has become a common practice across the African continent The Global Financial Integrity 2019 discovers that between 1980 and 2009 illicit financial outflows from Africa amounted to US 1 22 1 35 trillion Evidence shows that illicit financial flow out of the continent is associated with extractive industries and natural resources generally Nigeria is one of the resource rich countries crippling with the effects of capital flight in Africa Despite the absence of concrete studies on the scale and scope of this condition in Nigeria1 it is critical to unpack the underlying challenges and contributing factors the practice across a spectrum of institutional arrangements rules and political commitment to lesser extent This short paper sheds light on the illicit financial flows in the context of extractive industries and unpacks factors associated with absence of effective anti-corruption measures and poor governance of extractive industries